2012
DOI: 10.1007/s00259-012-2294-6
|View full text |Cite
|
Sign up to set email alerts
|

Diuretic 18F-FDG PET/CT imaging for detection and locoregional staging of urinary bladder cancer: prospective evaluation of a novel technique

Abstract: Diuretic (18)F-FDG PET/CT is highly sensitive and specific and plays an important role in improving detection of the primary tumour and locoregional staging of urinary bladder tumours. Diuretic (18)F-FDG PET/CT demonstrated a higher diagnostic value when compared with CECT in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 16 publications
0
48
0
2
Order By: Relevance
“…Recent studies of PET/CT using this approach have shown that bladder tumors indeed are consistently FDG avid and can be well visualized by PET. 12,13 In addition, small metastatic pelvic lymph nodes have been reported to exhibit increased activity using 18 F-FDG PET/CT, further supporting the potential value of PET for bladder cancer assessment. 14,15 …”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Recent studies of PET/CT using this approach have shown that bladder tumors indeed are consistently FDG avid and can be well visualized by PET. 12,13 In addition, small metastatic pelvic lymph nodes have been reported to exhibit increased activity using 18 F-FDG PET/CT, further supporting the potential value of PET for bladder cancer assessment. 14,15 …”
mentioning
confidence: 85%
“…A number of investigations have explored a forced diuresis protocol entailing, most commonly, oral hydration, IV diuretic administration, and subsequent voiding, performed between radiotracer administration and PET imaging. 9,11,12 This approach is intended to achieve clearance of excreted FDG from the bladder lumen while allowing for persistent uptake within the bladder wall itself. Recent studies of PET/CT using this approach have shown that bladder tumors indeed are consistently FDG avid and can be well visualized by PET.…”
mentioning
confidence: 99%
“…The optimum or specific isotope for studying bladder cancer has not yet been determined (34 (15,(35)(36)(37)(38). FDG is still the most widely used isotope to investigate bladder cancer (34).…”
Section: Transurethral Resectionmentioning
confidence: 99%
“…Ancak, oral hidrasyon, intravenöz diüretik kullanımı ve miksiyon sonrasında mesane lümenine uzanan mural lezyonlarda fokal FDG tutulumu izlenebilmekte, mesane kanserlerinin bölgesel değerlendirmesi kısmen yapılabilmektedir (123). Yine de FDG PET görüntülemenin mesane kanserlerinde esas rolü, uzak metastaz varlığının araştırılması, cerrahi sonrası rekürren hastalık varlığının belirlenmesi ve neoadjuvan kemoterapi yanıtının değerlendirilmesidir (14).…”
Section: Mesanekanserindepet/mrunclassified